Multirobot navigation functions I - Kyriakopoulos, Kostas J.; Loizou, Savvas (My University, 2006)
This is the first of two chapters dealing with multirobot navigation. In this chapter a centralized methodology is presented for navigating a team of multiple robotic agents. The solution is a closed form feedback based navigation scheme. The considered robot kinematics include holonomic and non-holonomic constraints and are handled under the unifying framework of multirobot navigation functions. The derived methodology has theoretically guaranteed global convergence and collision avoidance properties. The feasibility of the proposed navigation scheme is verified through non-trivial computer simulations.
Keywords: Robots--Kinematics; Feedback control systems; Navigation